If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = x(4 + -1x) 13 = (4 * x + -1x * x) 13 = (4x + -1x2) Solving 13 = 4x + -1x2 Solving for variable 'x'. Reorder the terms: 13 + -4x + x2 = 4x + -4x + -1x2 + x2 Combine like terms: 4x + -4x = 0 13 + -4x + x2 = 0 + -1x2 + x2 13 + -4x + x2 = -1x2 + x2 Combine like terms: -1x2 + x2 = 0 13 + -4x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-13' to each side of the equation. 13 + -4x + -13 + x2 = 0 + -13 Reorder the terms: 13 + -13 + -4x + x2 = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -4x + x2 = 0 + -13 -4x + x2 = 0 + -13 Combine like terms: 0 + -13 = -13 -4x + x2 = -13 The x term is -4x. Take half its coefficient (-2). Square it (4) and add it to both sides. Add '4' to each side of the equation. -4x + 4 + x2 = -13 + 4 Reorder the terms: 4 + -4x + x2 = -13 + 4 Combine like terms: -13 + 4 = -9 4 + -4x + x2 = -9 Factor a perfect square on the left side: (x + -2)(x + -2) = -9 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 45+0.25m=70+0.15m | | 2f+18=14 | | 2x+y-2z=14 | | V-4v+9=b-12 | | 3z+(-2)=8 | | 35-8r=-r+3(-3+5r) | | 5(2-x)-3(4-2x)=12 | | 0=-0.08t^2+4.48 | | 6(12x+1)=72x-2 | | 8r+8-3r=7r | | 6p(5p)= | | 10+15h=-5 | | 0.4(r+6)=0.63 | | 7d-d-6d-7-5d=0 | | X(y)=125 | | 5x=12x+14 | | 2n(1)= | | g(-6m)=-6m^2+5(-6m) | | -7+b-4=b-12 | | 9x+26+7x-17=2x+(3x)+5x | | 2(2.5+8.5)=-28.5 | | 7x^2-10=11 | | 1.5-2=b | | 200=6t+.75t^2 | | 4x+84=x+36 | | 0=18x^2+9+0 | | -X-y+2z=-13 | | 0=12x^2+9x+4 | | -3x+15y=5 | | 12x+9y=594 | | 588=6.50x+8.25y | | B+15=8b+8 |